Peruvian medicine during the century 1856 - 1956 - Espejo, Luis (1956)
The National Academy of Medicine gleefully adheres to cultural institutions homage rendered to the Faculty of Medicine of Lima, the honor of the Universidad Mayor de San Marcos, on the occasion of the celebration of its centenary.